1982
DOI: 10.1111/j.1365-2621.1982.tb07687.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Salmonella in Fresh Pork Sausage in 1979 Compared with 1969

Abstract: A Salmonella survey was conducted to determine its incidence in fresh pork sausage. Retail size samples representing different days of production were collected from 40 federally inspected plants and analyzed for the presence of salmonellae. The results obtained during the 1979 survey were compared to results obtained in a similar 1969 survey. Salmonellae were isolated from 162 of the 566 (28.6%) samples analyzed in 1969. For the samples analyzed in 1979, 74 of 603 samples (12.4%) were positive for salmonellae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…High incidences of contamination of fresh pork sausages with Salmonella have been reported, ranging from 30-65% (5,16) in the United Kingdom and 12-38% in the United States (13,17,20). The incidence of Salmonella contamination in sausages in this study (6-15%) falls in the lower levels of the latter range.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…High incidences of contamination of fresh pork sausages with Salmonella have been reported, ranging from 30-65% (5,16) in the United Kingdom and 12-38% in the United States (13,17,20). The incidence of Salmonella contamination in sausages in this study (6-15%) falls in the lower levels of the latter range.…”
Section: Discussionmentioning
confidence: 40%
“…The incidence of Salmonella contamination in sausages in this study (6-15%) falls in the lower levels of the latter range. It is of interest that Salmonella brandenburg (which was isolated more than any other Salmonella serotype) and S. bredeny have not been isolated from sausages in surveys made by British and American workers (5,13,16,17,20). There appeared to be no correlation between the presence of Salmonella and other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, they differ considerably in relation to S. derby, which was never isolated in our survey despite its frequent occurrence in swine (3,8,19) and pork products (2,9). In our study, S. cholerae-suis was isolated only twice, one strain belonging to the kunzendorf(monophasic variety) and the other one to the america type (biphasic variety); such a relatively low frequency seems to be in accordance with other investigations from different parts of the world (5,19).…”
Section: T H E V E T E Rmentioning
confidence: 71%
“…A later report by Surkiewicz et al (1972) placed the level of contamination of fresh pork sausage at 28.6%. The study of Johnston et al (1982) found that 12.4% of the samples tested were positive for Salmonella; however, all samples were frozen before isolation which could have affected the results due to freeze injury. Obviously the specific methodology used for the assay would affect the final result.…”
Section: Resultsmentioning
confidence: 99%
“…Accepted February 14, 1984 tested were positive for Salmonella. Johnston et al (1982) performed a survey and compared their findings with previous investigations to determine trends in the prevalence of Salmonella species in fresh pork sausage over the years of study. This study put the level of contamination at only 12% and concluded that a decrease in the prevalence of Salmonella in fresh pork sausage did exist.…”
Section: Introductionmentioning
confidence: 99%